"Mitos Ocidentais" e Cosmologias Ameríndias: Sobre a relação Homem/Natureza - Moro Martins, Homero (Revista Vernáculo, 2002)
"Mitos Ocidentais" e Cosmologias Ameríndias: Sobre a relação Homem/Natureza